Modeling hole size, lifetime and fuel consumption in hot-water ice drilling. Issue 68 (2014) - Greenler, L.; Benson, T.; Cherwinka, J.; Elcheikh, A.; Feyzi, F.; Karle, A.; Paulos, R.
Abstract: IceCube, a cubic-kilometer neutrino detector, was built at the South Pole using a hot-water drill system. Deep holes were drilled into the Antarctic ice sheet and filled with highly sensitive optical instrumentation. For the hot-water drilling, a computer model was developed to predict the hole sizes and hole lifetimes during construction. The goal was to predict ultimate size and freezeback rates based on water flow rate and temperature, drill speed, ice temperature and ream parameters (for a secondary operation where hot water continues to flow as the drill is withdrawn). This model proved to be very successful. It increased confidence that the holes would remain open long enough after drilling to allow the deployment of the necessary instrumentation. It also allowed for a decrease, over the course of the project, in the amount of overdrilling that was used as a margin against a too-rapid freeze-in. This resulted in significant fuel savings.